2021
DOI: 10.1021/acs.jafc.1c00784
|View full text |Cite
|
Sign up to set email alerts
|

Food Chemistry of Selenium and Controversial Roles of Selenium in Affecting Blood Cholesterol Concentrations

Abstract: Hypercholesterolemia, one of the major risk factors of cardiovascular diseases, is a worldwide public health problem. Nutraceuticals and phytochemicals are attracting attention as a result of their cholesterol-lowering ability and minimal side effects. Among them, selenium (Se) is on the list. The amount of Se in foods varies by region. Se-enriched fertilizers and feeds can raise the Se content in plants and animals, while some processing methods decrease food Se content. This review summarizes recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 115 publications
0
8
1
1
Order By: Relevance
“…In brook trout cells, cortisol secretion was restored by pregnenolone, suggesting that selenite impaired cortisol secretion in this cell line by disrupting pregnanolone synthesis. Pregnenolone is synthesized from cholesterol [ 243 ], and not only does selenium have a documented hypocholesterolemic effect, but the SELENOP receptor in the brain, LRP8, is heavily involved in cholesterol homeostasis, pointing towards a potential avenue for further investigation [ 244 , 245 ]. In the same study by Miller et al on rainbow trout cells, cortisol secretion was restored by N 6 ,2′-o-dibutyryladenosine 3′,5′-cyclic monophosphate (dbcAMP) [ 242 ].…”
Section: Signals From Brain To Bodymentioning
confidence: 99%
“…In brook trout cells, cortisol secretion was restored by pregnenolone, suggesting that selenite impaired cortisol secretion in this cell line by disrupting pregnanolone synthesis. Pregnenolone is synthesized from cholesterol [ 243 ], and not only does selenium have a documented hypocholesterolemic effect, but the SELENOP receptor in the brain, LRP8, is heavily involved in cholesterol homeostasis, pointing towards a potential avenue for further investigation [ 244 , 245 ]. In the same study by Miller et al on rainbow trout cells, cortisol secretion was restored by N 6 ,2′-o-dibutyryladenosine 3′,5′-cyclic monophosphate (dbcAMP) [ 242 ].…”
Section: Signals From Brain To Bodymentioning
confidence: 99%
“…Moreover, selenate preferentially adsorbed in an outer-sphere configuration at low pH, 33 which explains the low selectivity of Al 2 O 3 for selenate adsorption. 18,23 These findings beg two questions: (1) is the surface water network the sole controller of selenate adsorption on metal-oxide adsorbents 34 and (2) can interactions between the oxo anion and surface cations overcome the water network effects? 35−37 The importance of these questions is further highlighted by the recent work of Johnston and Chrysochoou who found that the adsorption mechanism of selenate and sulfate changes from inner-sphere to outer-sphere on naturally occurring Al substituted Fe (hydro)oxides at higher Al concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium is an essential micronutrient for all living beings; however, there is a narrow range between deficiency and toxicity. Consumption of selenium above 400 μg/day causes nausea, diarrhea, tachycardia and gastrointestinal disturbances and induces long-term effects like selenosis, hair loss, abnormal functioning of the nervous system, hepatotoxicity, etc. Leaching of selenium from anthropogenic practices such as agriculture irrigation, runoff from mining sites, e-waste landfills and natural reservoirs can cause high Se concentrations in drinking water. Once in the water, selenium oxidizes to its oxo-anion forms, selenate (Se­(VI) or SeO 4 2– ) or selenite (Se­(IV) or HSeO 3 – ), which are equally toxic to humans. Therefore, water treatment methods are required to decrease Se levels to below the EPA limit of 0.05 mg/L in water…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol, a key component of plasma components and membrane lipids, is indispensable for cells to grow and propagate(Garcia-Bermudez et al, 2019;Ma et al, 2019). However, the increased blood cholesterol is closely associated with atherosclerosis(Zhao et al, 2021). Therefore, Hong et al reported CuO NPs as POD-like nanozymes.…”
mentioning
confidence: 99%